Food-grade acid and alkali corrosion resistant silica gel material and preparation method thereof
Patent Information
- Application Number
- CN202611118197.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-27
- Publication Date
- 2026-10-23
AI Technical Summary
但两项技术仅采用无机填料实现耐酸碱改性,缺乏连续有机骨架支撑结构,仅依靠无机颗粒简单填充形成物理阻隔,内部易存留连通毛细渗透通道、长效耐酸碱渗透防护效果存在上限
[0024](1)本发明创造性结合二氧化硅刚性、纤维素柔性的结构特性,解决了单一无机填料结构不连续、韧性差、长期耐蚀稳定性不足的痛点,大幅拓宽了食品级硅胶材料的适用场景。
Smart Images

Figure CN122958873A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicone material preparation, and in particular to a food-grade acid and alkali resistant silicone material and its preparation method. Background Technology
[0002] In the iterative upgrading of food packaging materials, food-grade silicone has stood out due to its unique properties, becoming a core candidate material to replace traditional plastics such as PP and PS. Compared with PP and PS, food-grade silicone has unparalleled safety. Its main components, silicon and oxygen, do not release harmful substances such as bisphenol A and plasticizers at extreme temperatures, fully complying with stringent food contact safety standards such as those of the FDA and the EU EFSA. Furthermore, silicone possesses wide temperature stability from -40℃ to 250℃, capable of withstanding high-temperature cooking and baking, as well as long-term storage of frozen foods. In contrast, PP's heat resistance limit is only about 130℃, and PS is prone to brittleness at low temperatures. Therefore, silicone shows broad application prospects in the food packaging field.
[0003] However, the currently widely used food-grade silicone materials still have the following defects, which seriously restrict their application in acidic and alkaline food packaging scenarios: First, in order to reduce costs and improve mechanical properties, existing silicone formulations add a large amount of fillers such as calcium carbonate, aluminum hydroxide, and silica. These fillers are chemically unstable and are prone to chemical reactions when in contact with acidic foods such as vinegar and lemon juice, leading to filler dissolution, destruction of the silicone structure, and problems such as material expansion and cracking. Second, silicon-oxygen bonds are easily broken in alkaline environments, which damages the cross-linked structure of silicone, resulting in the material becoming soft and sticky, and unable to effectively package alkaline foods such as pickled vegetables and alkaline seasonings. Third, the nanoparticles added to improve the mechanical properties of silicone have a large specific surface area and strong electrostatic and intermolecular forces between particles, making them prone to agglomeration during physical blending. They are difficult to disperse evenly in the silicone matrix, resulting in stress concentration inside the material and a significant decrease in mechanical properties such as tensile strength and toughness.
[0004] To address the aforementioned shortcomings, existing research has shown that functionalizing inorganic nanoparticles can improve their hydrophobicity, reduce their aggregation tendency, and decrease the surface energy of the coating. Furthermore, constructing a dense cross-linked network between inorganic nanomaterials and silicone can effectively block the erosion paths of acid and alkali droplets through a synergistic effect. For example, patent CN120758166A discloses a multifunctional organosilicon coating that uses a composite of α,ω-terminated hydroxyl polydimethylsiloxane and α,ω-terminated hydroxyl polyphenylsiloxane as a matrix, combined with nanoparticles... Fillers such as powders and flame-retardant environmentally friendly inorganic powders, combined with long-chain amine small-molecule additives, construct a dual anti-corrosion mechanism of slow chemical neutralization and physical barrier. The resulting coatings possess flame retardancy, acid and alkali corrosion resistance, non-stick properties, good strength and elasticity, and weather resistance. Patent CN118791877B discloses an acid and alkali resistant silicone tube and its preparation method. Using methyl vinyl silicone rubber as the matrix, it introduces self-made modified graphitic carbon nitride as a functional filler, combined with additives such as silica, polymethylhydrosiloxane, vulcanizing agent, and platinum catalyst. The finished product is obtained through mixing, extrusion, and vulcanization processes. Testing confirms that modified graphitic carbon nitride can significantly improve the acid / alkali corrosion resistance of silicone tubes. However, both technologies only use inorganic fillers to achieve acid and alkali resistance modification, lacking a continuous organic framework support structure. They rely solely on simple inorganic particle filling to form a physical barrier, which easily leaves interconnected capillary permeation channels inside, limiting the long-term acid and alkali permeation protection effect. Furthermore, neither technology is designed for food-grade applications and suffers from common limitations such as unverified raw material safety, the inability of traditional silicone fillers to withstand acids and alkalis, and unreliable nanoparticle dispersion, making them difficult to apply directly to the food packaging field. Therefore, developing a food-grade silicone material with acid and alkali corrosion resistance and good mechanical properties, along with its preparation method, has significant practical importance and market value. Summary of the Invention
[0005] This invention addresses the shortcomings of existing technologies by providing a food-grade acid and alkali resistant silicone material. This improves the stability of silicone materials in strong acid and alkali environments, prevents structural damage and performance degradation caused by the poor acid resistance of fillers and easy hydrolysis of molecular chains in traditional silicone, and also takes into account the mechanical properties of the material, thus meeting the urgent needs of the food packaging industry for safe, durable, and multifunctional materials.
[0006] To achieve the above objectives, the technical solution adopted by this invention is: a method for preparing food-grade acid and alkali resistant silicone material, characterized by the following steps: methyl vinyl silicone is fed into a mixer, followed by the addition of premixed double-modified silica filler and double-modified cellulose particles in three separate batches. After uniform mixing, the mixture is cooled and transferred to a two-roll mill. Hydrogen-containing silicone oil, inhibitor, and catalyst are added sequentially, and the mixture is further mixed until uniform. The mixture is then pre-pressed and subjected to high-temperature vulcanization to obtain the food-grade acid and alkali resistant silicone material. The components, by weight, include 100 parts methyl vinyl silicone, 30-50 parts double-modified silica filler, 15-25 parts double-modified cellulose particles, 4-10 parts hydrogen-containing silicone oil, 0.05-0.1 parts inhibitor, and 0.5-1 parts catalyst.
[0007] Preferably, the preparation method of the dual-modified silica filler includes:
[0008] S1.1 Double bond grafting: Nano-silica is ultrasonically dispersed in ethanol to prepare a dispersion of 0.5~2.0wt%. HCl is added to adjust the pH of the solution to 4~5. Then, a silane coupling agent with double bonds is added. The mixture is stirred at 60~90℃ for 4~8h. After the reaction is completed, the product is collected by centrifugation and repeatedly washed with ethanol to remove the silane coupling agent and other impurities. After drying at 60~100℃, the silica intermediate with surface grafted double bonds is obtained.
[0009] S1.2, Long-chain alkyl grafting: The silica intermediate obtained in step S1.1 is ultrasonically dispersed in an organic solvent to prepare a dispersion of 0.5~2.0 wt%. Then, straight-chain alkane thiols and photoinitiators are added, and the mixture is reacted under ultraviolet light for 10~30 min. After the reaction is completed, the product is collected by centrifugation and repeatedly washed with organic solvent to remove unreacted impurities. After drying at 60~100℃, the double-modified silica filler is obtained.
[0010] Preferably, the method for preparing dual-modified cellulose particles includes:
[0011] S2.1 Double bond grafting: 0.1~5μm nanocellulose particles are ultrasonically dispersed in ethanol to prepare a 0.5~2.0wt% dispersion. HCl is then added to adjust the pH of the solution to 4~5. Subsequently, a silane coupling agent with double bonds is added, and the reaction is stirred at 60~90℃ for 4~8h. After the reaction is completed, the product is collected by centrifugation and repeatedly washed with ethanol to remove the silane coupling agent and other impurities. After drying at 60~100℃, the cellulose particle intermediate with surface grafted double bonds is obtained.
[0012] S2.2, Long-chain alkyl grafting: The cellulose particle intermediate obtained in step S2.1 is ultrasonically dispersed in an organic solvent to prepare a dispersion of 0.5~2.0 wt%. Then, straight-chain alkane thiols and a photoinitiator are added, and the mixture is reacted under ultraviolet light for 10~30 min. After the reaction, the product is collected by centrifugation and repeatedly washed with an organic solvent to remove unreacted impurities. The product is then dried at 60~100℃ to obtain the double-modified cellulose particles. The nanocellulose particles are commercially available cellulose powder obtained after acid hydrolysis, with a particle size of 2-20 μm.
[0013] Preferably, the silane coupling agent with double bonds is at least one of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane; the straight-chain alkane thiol is at least one of dodecanethiol, tridecanethiol, tetradecanethiol, pentadecanethiol, hexadecethiol, heptadecanethiol, and octadecethiol; the organic solvent is any one of anhydrous ethanol, tetrahydrofuran, acetone, and toluene; and the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone or 1-hydroxycyclohexylphenyl ketone.
[0014] Preferably, the amount of the silane coupling agent with double bonds added is 10-30% of the mass of nano-silica.
[0015] Preferably, the molar ratio of the added straight-chain alkane thiol to the silane coupling agent with double bonds is 0.5 to 1.
[0016] Preferably, the amount of photoinitiator added is 1 to 2 wt% of the total mass of the silica intermediate and the straight-chain alkane thiol.
[0017] Preferably, the catalyst is a Karstedt catalyst with a content of 1000~3000 ppm based on platinum; the inhibitor is acetylenecyclohexanol.
[0018] Preferably, the vulcanization process includes a first-stage vulcanization and a second-stage vulcanization. The temperature of the first-stage vulcanization is 165~175℃, and the time of the first-stage vulcanization is 20~30 min. The temperature of the second-stage vulcanization is 210~220℃, and the time of the second-stage vulcanization is 1.5~2 h. The speed of the internal mixer is 40 rpm, and the speed of the open mill is 15 rpm.
[0019] A food-grade acid and alkali resistant silicone material is prepared using any one of the above-described methods for preparing a food-grade acid and alkali resistant silicone material.
[0020] The core of this invention is to dual-modify nano-silica and micro / nano-cellulose particles through a two-step precise reaction, endowing silica materials with excellent acid and alkali resistance. Existing similar acid and alkali resistant silica patents only use pure inorganic fillers for modification, relying solely on the dotted filling of inorganic particles for seepage prevention, resulting in defects such as discontinuous structure, poor toughness, and insufficient long-term corrosion resistance. This invention innovatively adopts a synergistic system of cellulose and silica composites, utilizing the unique long-chain skeleton advantage of cellulose to compensate for the structural shortcomings of pure inorganic fillers, combined with the rigid filling characteristics of silica, to achieve complementary and synergistic performance. The first step utilizes a hydrolysis-condensation reaction to graft a silane coupling agent with double bonds onto the surface of nano-silica and micro / nano-cellulose. The original surfaces of silica and cellulose contain a large number of active hydroxyl groups. In a suitable aqueous environment, the silane coupling agent undergoes hydrolysis to generate silanol hydrolysis products, which then undergo a condensation reaction with the hydroxyl groups on the surface of silica and cellulose. Through stable silicon-oxygen bonds, the double bond groups are covalently bound to the surface of silica and cellulose, constructing key active sites for subsequent modification. The second step involves grafting straight-chain alkane thiols via a mercaptoene click reaction. Under ultraviolet light initiation, the thiol groups in the thiol molecules undergo an efficient addition reaction with the double bonds on the surfaces of silica and cellulose to form stable carbon-sulfur bonds. This successfully grafts long-chain alkyl groups onto the surfaces of silica and cellulose, endowing them with unique hydrophobic properties.
[0021] The dual-modified silica and cellulose play a triple key role in the silica gel system. First, the long-chain alkyl groups grafted onto the surface have extremely low surface energy, which significantly improves the overall hydrophobicity of the silica gel. When acid and alkali droplets come into contact with the material surface, due to the huge difference in surface energy, the droplets exhibit a high contact angle, making it difficult for them to spread and wet. This reduces the direct contact between the corrosive medium and the silica gel matrix from the source, effectively blocking the initial penetration of acid and alkali droplets. Second, the double bonds remaining on the surface of modified silica and cellulose can serve as inorganic cross-linking points, participating in hydrosilylation reactions and undergoing multiple cross-linking with the vinyl groups in methyl vinyl silica gel and the hydrogen silane bonds in hydrogen-containing silicone oil, constructing a dense organic-inorganic hybrid network structure. Cellulose can form a continuous overall cross-linked network by connecting the discrete silica cross-linking sites in series with its long-chain structure, solving the drawbacks of fragmented cross-linking and weak interfacial bonding of single inorganic fillers. This highly cross-linked structure not only enhances the material's mechanical stability but also forms a physical barrier, effectively extending the penetration path of acidic and alkaline media and slowing down the corrosion process. Thirdly, silica has a stable structure, making it difficult to corrode in acidic and alkaline media and exhibiting significant rigidity, while the long-chain structure of cellulose molecules demonstrates good flexibility. By cleverly combining the respective mechanical property advantages of cellulose and silica, the drawbacks of traditional single inorganic filler-modified silica gel—high rigidity, poor toughness, susceptibility to microcracks, and severe mechanical property degradation under long-term acidic and alkaline conditions—are solved. A synergistic balance between rigidity and flexibility is achieved, significantly improving the overall acid and alkali resistance and service stability of the material.
[0022] Furthermore, the reaction process of this invention is simple and controllable, requiring no complex equipment or harsh conditions, and is easy to implement for large-scale industrial production. The two-stage vulcanization process employed is the core step in ensuring food-grade quality. The first stage of vulcanization achieves preliminary solidification of the material, forming a basic cross-linked structure; the second stage of high-temperature vulcanization further promotes deep cross-linking of the system, while thoroughly removing small molecule volatiles from the material, ensuring that the material is odorless and free of harmful residues, meeting the high purity requirements for food-grade products.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) This invention creatively combines the rigidity of silica and the flexibility of cellulose to solve the problems of discontinuous structure, poor toughness and insufficient long-term corrosion resistance of single inorganic fillers, and greatly expands the application scenarios of food-grade silicone materials.
[0025] (2) This invention introduces dual-modified silica filler and cellulose particles to construct a dual corrosion resistance mechanism of hydrophobic surface and dense cross-linked structure. Long-chain alkyl groups endow the material with high hydrophobicity, reducing the wetting of acid and alkali droplets; the organic-inorganic hybrid cross-linked network constructs a physical barrier, extending the medium penetration path. The superposition of the dual mechanism enables the material to maintain structural stability and performance integrity in strong acid, strong alkali and alternating corrosion environments.
[0026] (3) The dual modification treatment of the present invention improves the dispersibility of nano-silica and cellulose in the silica matrix, and achieves the tight combination of inorganic filler and organic matrix through multiple cross-linking reaction, thereby enhancing the corrosion resistance and improving the mechanical properties of the material at the same time; and the preparation process is simple and controllable, and the two-stage vulcanization process ensures food-grade purity, making it easy for industrial large-scale production. Attached Figure Description
[0027] Figure 1 Infrared spectra of the original cellulose particles, the cellulose intermediate prepared in Example 1, and the double-modified cellulose particles.
[0028] Figure 2 Scanning electron microscope images of the original cellulose particles and the dual-modified cellulose particles prepared in Example 1, at magnifications of 1000x.
[0029] Figure 3 Contact angle diagrams for pure silicone and the food-grade acid and alkali resistant silicone material prepared in Example 1. Detailed Implementation
[0030] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0031] This invention uses nano-silica and micro / nano-cellulose as fillers. Through hydrolysis-condensation and mercaptoene click reactions, double bonds and long alkane chains are sequentially introduced onto the surfaces of silica and cellulose. These are then mixed with food-grade silica gel and prepared using a two-stage vulcanization process to produce an acid and alkali resistant material. On one hand, the high hydrophobicity imparted by the long-chain alkyl groups and the physical barrier constructed by the organic-inorganic hybrid crosslinking network not only solve the problem of single inorganic fillers easily failing in alternating acid and alkali environments, but also prevent the penetration of corrosive media and delay the corrosion process from the source, significantly broadening the material's application scenarios. On the other hand, the dual modification treatment improves the dispersibility of nano-silica and cellulose in the matrix, and the multiple crosslinking reactions achieve a tight bond between the inorganic filler and the organic matrix. This enhances corrosion resistance while simultaneously optimizing the material's mechanical properties. Furthermore, the preparation process is simple and controllable, and the two-stage vulcanization process ensures food-grade purity, facilitating large-scale industrial production.
[0032] Example 1
[0033] Preparation of dual-modified silica filler: 5g of nano-silica was ultrasonically dispersed in 500g of ethanol, and the pH was adjusted to 4 with HCl. Then, 2g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was stirred at 80℃ for 6h. After the reaction, the product was collected by centrifugation, washed repeatedly with anhydrous ethanol, and dried at 80℃ to obtain a silica intermediate. 5g of the intermediate was ultrasonically dispersed in 500g of anhydrous ethanol, and 2g of octadecyl mercaptan and 0.07g of 2-hydroxy-2-methyl-1-phenyl-1-propanone were added. The mixture was irradiated with ultraviolet light for 20min. The product was collected by centrifugation, washed with anhydrous ethanol, and dried at 80℃ to obtain the dual-modified silica filler.
[0034] Preparation of dual-modified cellulose particles: 5g of nanocellulose particles were ultrasonically dispersed in 500g of ethanol, and the pH was adjusted to 4 with HCl. Then, 2g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was stirred at 80℃ for 6h. After the reaction, the product was collected by centrifugation, washed repeatedly with anhydrous ethanol, and dried at 80℃ to obtain a cellulose particle intermediate. 5g of the intermediate was ultrasonically dispersed in 500g of anhydrous ethanol, and 2g of octadecyl mercaptan and 0.07g of 2-hydroxy-2-methyl-1-phenyl-1-propanone were added. The mixture was irradiated with ultraviolet light for 20min. The product was collected by centrifugation, washed with anhydrous ethanol, and dried at 80℃ to obtain the dual-modified cellulose particle filler.
[0035] Preparation of food-grade acid and alkali resistant silicone material: 100 parts of methyl vinyl silicone were put into a 40 rpm internal mixer. Then, 40 parts of double-modified silica filler and 20 parts of double-modified cellulose particles were premixed and added to the internal mixer in three batches at 3 min intervals. After mixing evenly at 80°C, the mixture was cooled to 35°C and transferred to an open mill. 7 parts of hydrogen-containing silicone oil, 0.05 parts of acetylenecyclohexanol and 0.8 parts of Karstedt catalyst were added in sequence. The mixture was continued to be mixed at 15 rpm until uniform. The mixture was pre-pressed at 0.08 MPa and then vulcanized at 170°C for 25 min and at 215°C for 1.75 h to obtain food-grade acid and alkali resistant silicone material.
[0036] Figure 1 Infrared spectra of pristine cellulose particles, the cellulose intermediate prepared in Example 1, and the doubly modified cellulose particles. Compared to pristine cellulose, the cellulose intermediate exhibits... A distinct C=O stretching vibration peak appears at 2920 and... The presence of stretching vibration peaks at the CH bonds of methyl and methylene groups indicates that γ-methacryloyloxypropyltrimethoxysilane was successfully grafted onto the cellulose intermediate; further reaction revealed peaks at 2920 and... The CH stretching vibration peak at that location was significantly enhanced, while at... The peak intensity of the CH bending vibration at the location was synchronously enhanced. This proves that the cellulose intermediate and octadecyl mercaptan successfully under ultraviolet light irradiation undergo a mercaptoene reaction, introducing a large number of long alkane chains onto the cellulose surface, which plays a key role in reducing the surface energy of food-grade silicone materials.
[0037] Figure 2 Scanning electron microscope (SEM) images of the original cellulose particles and the double-modified cellulose particles prepared in Example 1. It can be seen that the cellulose particles largely retain their original morphology after modification, with a thin octadecyl mercaptan layer grafted onto the surface. This addition effectively improves the alkali resistance and mechanical strength of the food-grade silica gel material.
[0038] Figure 3 The contact angle diagrams are for pure silica gel and the food-grade acid and alkali resistant silica gel material prepared in Example 1. The surface contact angle of pure silica gel is 96°, while the surface contact angle of the silica gel coating with added double-modified silica filler and cellulose particles is increased to 110°. Therefore, acid and alkali droplets are difficult to spread and wet on its surface, effectively blocking the initial penetration of acid and alkali droplets, thereby improving acid and alkali resistance.
[0039] Example 2
[0040] Preparation of dual-modified silica filler: 2.5 g of nano-silica was ultrasonically dispersed in 500 g of ethanol, and the pH was adjusted to 5 with HCl. Then, 2 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was stirred at 60 °C for 8 h. After the reaction, the product was collected by centrifugation, washed repeatedly with anhydrous ethanol, and dried at 60 °C to obtain a silica intermediate. 2.5 g of the intermediate was ultrasonically dispersed in 500 g of anhydrous ethanol, and 2 g of pentadecyl mercaptan and 0.07 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone were added. The mixture was irradiated with ultraviolet light for 10 min. The product was collected by centrifugation, washed with anhydrous ethanol, and dried at 60 °C to obtain the dual-modified silica filler.
[0041] Preparation of dual-modified cellulose particles: 2.5 g of nanocellulose particles were ultrasonically dispersed in 500 g of ethanol, and the pH was adjusted to 5 with HCl. Then, 2 g of γ-methacryloyloxypropyltrimethoxysilane was added, and the mixture was stirred at 60 °C for 8 h. After the reaction, the product was collected by centrifugation, washed repeatedly with anhydrous ethanol, and dried at 60 °C to obtain a cellulose particle intermediate. 2.5 g of the intermediate was ultrasonically dispersed in 500 g of anhydrous ethanol, and 2 g of pentadecyl mercaptan and 0.07 g of 2-hydroxy-2-methyl-1-phenyl-1-propanone were added. The mixture was irradiated with ultraviolet light for 10 min. The product was collected by centrifugation, washed with anhydrous ethanol, and dried at 60 °C to obtain the dual-modified cellulose particle filler.
[0042] Preparation of food-grade acid and alkali resistant silicone material: 100 parts of methyl vinyl silicone were put into a 40 rpm internal mixer. Then, 30 parts of double-modified silica filler and 15 parts of double-modified cellulose particles were premixed and added to the internal mixer in three batches (3 min apart). After mixing evenly at 80°C, the mixture was cooled to 35°C and transferred to a two-roll mill. 4 parts of hydrogen-containing silicone oil, 0.05 parts of acetylenecyclohexanol and 0.5 parts of Karstedt catalyst were added in sequence. The mixture was continued to be mixed at 15 rpm until uniform. The mixture was pre-pressed at 0.08 MPa and then vulcanized at 165°C for 20 min and at 210°C for 1.5 h to obtain food-grade acid and alkali resistant silicone material.
[0043] Example 3
[0044] Preparation of dual-modified silica filler: 10g of nano-silica was ultrasonically dispersed in 500g of ethanol, the pH was adjusted to 5 with HCl, and 5g of vinyltriethoxysilane was added. The mixture was stirred at 90℃ for 8h. After centrifugation, washing with ethanol, and drying at 100℃, a silica intermediate was obtained. 10g of the intermediate was ultrasonically dispersed in 500g of toluene, 5g of dodecanethiol and 0.3g of 1-hydroxycyclohexylphenyl ketone were added, and the mixture was irradiated with ultraviolet light for 30min. After centrifugation, washing with toluene, and drying at 100℃, the dual-modified silica filler was obtained.
[0045] Preparation of dual-modified cellulose particles: 10g of nanocellulose particles were ultrasonically dispersed in 500g of ethanol, the pH was adjusted to 5 with HCl, and 5g of vinyltriethoxysilane was added. The mixture was stirred at 90℃ for 8h. After centrifugation, washing with ethanol, and drying at 100℃, a silica intermediate was obtained. 10g of the intermediate was ultrasonically dispersed in 500g of toluene, and 5g of dodecanethiol and 0.3g of 1-hydroxycyclohexylphenyl ketone were added. The mixture was irradiated with ultraviolet light for 30min. After centrifugation, washing with toluene, and drying at 100℃, a dual-modified silica filler was obtained.
[0046] Preparation of food-grade acid and alkali resistant silicone material: 100 parts of methyl vinyl silicone were put into a 40 rpm internal mixer. Then, 50 parts of double-modified silica filler and 25 parts of double-modified cellulose particles were premixed and added to the internal mixer in three batches (3 min apart). After mixing evenly at 80°C, the mixture was cooled to 35°C and transferred to a two-roll mill. 10 parts of hydrogen-containing silicone oil, 0.1 parts of acetylene cyclohexanol and 1 part of Karstedt catalyst were added in sequence. The mixture was continued to be mixed at 15 rpm until uniform. The mixture was pre-pressed at 0.08 MPa and then vulcanized at 175°C for 30 min and at 220°C for 2 h to obtain food-grade acid and alkali resistant silicone material.
[0047] Example 4
[0048] The preparation methods for the dual-modified silica filler and cellulose particles are the same as in Example 3.
[0049] Food-grade acid and alkali resistant silicone material is prepared by the following method: 100 parts of methyl vinyl silicone are put into a 40 rpm internal mixer, followed by 45 parts of double-modified silica filler and 18 parts of double-modified cellulose particles premixed and added to the internal mixer in three batches (3 min apart each time). After mixing evenly at 80°C, the mixture is cooled to 35°C and transferred to an open mill. 8 parts of hydrogen-containing silicone oil, 0.08 parts of acetylenecyclohexanol and 1 part of Karstedt catalyst are added sequentially, and mixing is continued at 15 rpm until uniform. The mixture is pre-pressed at 0.08 MPa and then vulcanized in one stage at 175°C for 25 min and in the second stage at 220°C for 1.5 h to obtain food-grade acid and alkali resistant silicone material.
[0050] Comparative Example 1
[0051] This comparative example provides a method for preparing food-grade acid and alkali resistant silica gel material: the double-modified silica filler and cellulose particles in Example 1 are replaced with silica intermediates and cellulose intermediates grafted with only double bonds, and everything else is completely the same as in Example 1.
[0052] Comparative Example 2
[0053] This comparative example provides a method for preparing food-grade acid and alkali resistant silica gel material: the double-modified cellulose particles in the formulation of Example 1 are deleted, the amount of double-modified silica added is changed to 60 parts, and everything else is completely the same as in Example 1.
[0054] Comparative Example 3
[0055] This comparative example provides a method for preparing food-grade acid and alkali resistant silica gel material: the double-modified silica filler in the formulation of Example 1 is deleted, the amount of double-modified cellulose particles added is changed to 60 parts, and everything else is completely the same as in Example 1.
[0056] Comparative Example 4
[0057] This comparative example provides a method for preparing food-grade acid and alkali resistant silica gel material: the double-modified silica filler in Example 1 is replaced with commercially available hydrophobic nano-silica, with an addition amount of 60 parts. The double-modified cellulose particles in the formula are deleted, and everything else is completely consistent with Example 1.
[0058] The following performance tests were conducted on the food-grade acid and alkali resistant silicone materials prepared in the above embodiments and comparative examples. The experimental results are shown in Tables 1 and 2.
[0059] Acid corrosion resistance: Three samples from each sample were immersed in a 5% hydrochloric acid aqueous solution at room temperature for 7 days. Then, tensile tests were performed on the three samples to determine their mechanical properties and the average value was taken.
[0060] Alkali corrosion resistance: Three samples from each sample were immersed in a 5% sodium hydroxide aqueous solution at room temperature for 7 days. Then, tensile tests were performed on the three samples to determine their mechanical properties and the average value was taken.
[0061] Tensile strength: tested using an electronic tensile testing machine according to... The tensile properties of the standard test sample were measured at a rate of 500 mm / min.
[0062] Tear strength: according to The tear performance of the standard test sample is measured at a rate of 500 mm / min.
[0063] Hardness: Measured using a Shore A hardness tester according to... The hardness of the standard test sample.
[0064]
[0065] As shown in Table 1, the mechanical properties of the food-grade acid and alkali resistant silicone materials are closely related to the amount of double-modified silica filler, cellulose particles, and crosslinking agent added. Their tensile strength, tear strength, and hardness generally increase gradually with the increase of the amount of double-modified filler and the crosslinking density. The food-grade silicone materials prepared in Examples 1-4 all exhibit excellent mechanical properties, with tensile strength greater than 10 MPa, tear strength higher than 30 kN / m, and hardness higher than 60 A. This is because the silicone material system, through a strategy of double modification and multiple crosslinking, achieves chemical bonding and structural synergy between the filler and the matrix, significantly improving tensile and tear strength. Simultaneously, by introducing flexible cellulose to regulate hardness, the material maintains excellent mechanical properties while also possessing flexibility and corrosion resistance. After immersion in 5% hydrochloric acid and 5% sodium hydroxide solutions for 7 days, the food-grade silicone materials prepared in Examples 1-4 showed a tensile strength retention rate ≥97%, a tear strength retention rate ≥96%, and a hardness change ≤1 A, demonstrating excellent chemical stability. This invention involves dual modification of silica and cellulose to introduce active double bonds and hydrophobic alkane chains. On the one hand, this imparts high hydrophobicity to the silica material to reduce the wetting of acid and alkali droplets. On the other hand, it constructs a physical barrier of organic-inorganic hybrid cross-linked network to extend the medium penetration path. At the same time, the two-stage vulcanization process ensures network densification to achieve no reactive residue. The synergistic effect of these multiple factors gives the food-grade silica material excellent resistance to acid and alkali corrosion.
[0066]
[0067] The comparison results of the examples and comparative examples show that:
[0068] Compared to Example 1, Comparative Example 1 differs in that the modified silica filler and cellulose particles used in Comparative Example 1 only had double bonds grafted onto them. The resulting food-grade silicone material exhibited reduced tensile and tear strength, and its mechanical properties showed a significant decrease after treatment with acid and alkali solutions. This indicates that although the modified filler participates in cross-linking with double bonds in the silicone system, the residual small amount of hydroxyl groups may affect its dispersibility in the matrix, thereby reducing mechanical properties. Furthermore, the lack of a C18 hydrophobic layer in the modified filler also makes the resulting silicone material susceptible to attack by corrosive liquids, leading to structural damage. Especially in alkaline environments, the hydrophilic interface becomes a channel for alkali penetration, and hydrolysis reactions concentrate at the filler-matrix interface, resulting in interface debonding and microcrack propagation.
[0069] Compared to Example 1, Comparative Example 2 differs in that the filler in Comparative Example 2 contains only double-modified silica. Due to the high content of double-modified rigid silica, the tensile strength and hardness of the resulting food-grade silicone material are significantly improved, while the tear strength decreases due to the lack of flexible cellulose organic filler. Furthermore, although the food-grade silicone material exhibits excellent acid resistance, its mechanical properties significantly decrease after alkaline treatment. This indicates that when relying solely on a rigid silica network without a flexible toughening phase, the material is prone to crack propagation and structural relaxation in an alkaline environment.
[0070] Compared to Example 1, Comparative Example 3 differs in that the filler in Comparative Example 3 contains only double-modified cellulose particles. Although the cellulose is double-modified, its modulus is much lower than that of silica. The resulting food-grade silicone material is still dominated by a flexible network, resulting in a significant decrease in tensile strength and hardness, while its tear strength remains high. Furthermore, this food-grade silicone material exhibits unstable resistance to acid and alkali corrosion, especially in alkalis, where its mechanical properties degrade more than in acidic solutions. This is because although the hydrophobic layer of the double-modified cellulose can initially delay droplet penetration, it is still subject to acid and alkali attacks over time. The lack of a rigid framework in the material system leads to rapid softening of the silicone and the formation of structural defects.
[0071] Compared to Example 1, Comparative Example 4 differs in that it contains only hydrophobically modified fumed silica filler. This filler does not form chemical bonds within the silica matrix, resulting in weak adhesion and easy debonding at the interface due to stress. Consequently, the tensile and tear strengths of the resulting food-grade silica material are significantly reduced, while the hardness increases due to the accumulation of silica filler. Furthermore, since the silica filler and silica matrix are only bonded by van der Waals forces or physical entanglement, the food-grade silica material experiences rapid debonding at the interface after acid and alkali treatment, leading to a significant decrease in its mechanical properties. This is especially true in alkaline environments where the Si-O-Si network is more susceptible to attack and rapid failure.
[0072] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0073] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and variations without departing from the concept of the present invention, and these modifications all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.
Claims
1. A method for preparing a food-grade acid and alkali resistant silicone material, characterized in that: The material is prepared by the following steps: Methyl vinyl silica gel is put into an internal mixer, and then premixed double-modified silica filler and double-modified cellulose particles are added in three batches. After mixing evenly, the mixture is cooled and transferred to a two-roll mill. Hydrogen-containing silicone oil, inhibitor, and catalyst are added in sequence, and the mixture is continued to be mixed until uniform. The mixture is pre-pressed and subjected to high-temperature vulcanization treatment to obtain food-grade acid and alkali resistant silicone material. The components, by weight, include 100 parts of methyl vinyl silica gel, 30-50 parts of double-modified silica filler, 15-25 parts of double-modified cellulose particles, 4-10 parts of hydrogen-containing silicone oil, 0.05-0.1 parts of inhibitor, and 0.5-1 parts of catalyst.
2. The method for preparing a food-grade acid and alkali resistant silica gel material according to claim 1, characterized in that: The preparation method of the dual-modified silica filler includes: S1.1 Double bond grafting: Nano-silica is ultrasonically dispersed in ethanol to prepare a dispersion of 0.5~2.0wt%. HCl is added to adjust the pH of the solution to 4~5. Then, a silane coupling agent with double bonds is added. The mixture is stirred at 60~90℃ for 4~8h. After the reaction is completed, the product is collected by centrifugation and repeatedly washed with ethanol to remove the silane coupling agent and other impurities. After drying at 60~100℃, the silica intermediate with surface grafted double bonds is obtained. S1.2, Long-chain alkyl grafting: The silica intermediate obtained in step S1.1 is ultrasonically dispersed in an organic solvent to prepare a dispersion of 0.5~2.0 wt%. Then, straight-chain alkane thiols and photoinitiators are added, and the mixture is reacted under ultraviolet light for 10~30 min. After the reaction is completed, the product is collected by centrifugation and repeatedly washed with organic solvent to remove unreacted impurities. After drying at 60~100℃, the double-modified silica filler is obtained.
3. The method for preparing a food-grade acid and alkali resistant silica gel material according to claim 1, characterized in that: Methods for preparing dual-modified cellulose particles include: S2.1 Double bond grafting: 0.1~5μm nanocellulose particles are ultrasonically dispersed in ethanol to prepare a 0.5~2.0wt% dispersion. HCl is then added to adjust the pH of the solution to 4~5. Subsequently, a silane coupling agent with double bonds is added, and the reaction is stirred at 60~90℃ for 4~8h. After the reaction is completed, the product is collected by centrifugation and repeatedly washed with ethanol to remove the silane coupling agent and other impurities. After drying at 60~100℃, the cellulose particle intermediate with surface grafted double bonds is obtained. S2.2, Long-chain alkyl grafting: The cellulose particle intermediate obtained in step S2.1 is ultrasonically dispersed in an organic solvent to prepare a dispersion of 0.5~2.0 wt%. Then, straight-chain alkane thiols and photoinitiators are added, and the mixture is reacted under ultraviolet light for 10~30 min. After the reaction is completed, the product is collected by centrifugation and repeatedly washed with organic solvent to remove unreacted impurities. After drying at 60~100℃, the double-modified cellulose particles are obtained.
4. The method for preparing a food-grade acid and alkali resistant silicone material according to any one of claims 2-3, characterized in that: The silane coupling agent with double bonds is at least one of γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, vinyltrimethoxysilane, and vinyltriethoxysilane; the straight-chain alkane thiol is at least one of dodecanethiol, tridecanethiol, tetradecanethiol, pentadecanethiol, hexadecethiol, heptadecanethiol, and octadecethiol; the organic solvent is any one of anhydrous ethanol, tetrahydrofuran, acetone, and toluene; and the photoinitiator is 2-hydroxy-2-methyl-1-phenyl-1-propanone or 1-hydroxycyclohexylphenyl ketone.
5. The method for preparing a food-grade acid and alkali resistant silica gel material according to claim 4, characterized in that: The amount of the silane coupling agent with double bonds added is 10-30% of the mass of nano-silica.
6. The method for preparing a food-grade acid and alkali resistant silica gel material according to claim 4, characterized in that: The molar ratio of the added straight-chain alkane thiol to the double-bonded silane coupling agent is 0.5~1.
7. The method for preparing a food-grade acid and alkali resistant silica gel material according to claim 4, characterized in that: The amount of photoinitiator added is 1-2 wt% of the total mass of the silica intermediate and the straight-chain alkane thiol.
8. The method for preparing a food-grade acid and alkali resistant silica gel material according to claim 1, characterized in that: The catalyst is a Karstedt catalyst with a platinum content of 1000~3000 ppm; the inhibitor is acetylenecyclohexanol.
9. The method for preparing a food-grade acid and alkali resistant silica gel material according to claim 1, characterized in that: The vulcanization process includes a first-stage vulcanization and a second-stage vulcanization. The temperature of the first-stage vulcanization is 165~175℃ and the time is 20~30min. The temperature of the second-stage vulcanization is 210~220℃ and the time is 1.5~2h. The speed of the internal mixer is 40rpm and the speed of the open mill is 15rpm.
10. A food-grade acid and alkali resistant silicone material, characterized in that: It is prepared using the preparation method of the food-grade acid and alkali resistant silicone material according to any one of claims 1 to 9.
Citation Information
Patent Citations
Multifunctional organic silicon coating and preparation method thereof
CN120758166A